A root of less evil [digital signal processing]. - Allie, M.
This work discusses several methods for estimating the square root of a number, with particular focus on high-speed techniques for approximating the square root of a single value as well as the square root of a sum of squares for quadrature (I/Q) vector magnitude estimation. The paper presents the Newton-Raphson inverse method and the nonlinear IIR filter method for estimating the square root of a single value using iterative methods. It also presents the binary-shift magnitude estimation method and the equiripple-error magnitude estimation method for estimating the magnitude of a complex number.
Keywords: Complex vector magnitude approximation algorithm; Fixed point fractional binary arithmetic; High throughput algorithm; Iterative Newton Raphson inverse square root method; Nonlinear IRR filter (NIIRF) square root method